Infectious Disease and Primary Care Research-What English General Practitioners Say They Need - Donna M. Lecky; Steve Granier; Rosalie Allison; Neville Q. Verlander; Simon M. Collin; Cliodna A. M. McNulty (MDPI AG, 2020)
Background: Infections are one of the most common reasons for patients attending primary care. Antimicrobial resistance (AMR) is perhaps one of the biggest threats to modern medicine; data show that 81% of antibiotics in the UK are prescribed in primary care. Aim: To identify where the perceived gaps in knowledge, skills, guidance and research around infections and antibiotic use lie from the general practitioner (GP) viewpoint. Design and Setting: An online questionnaire survey. Method: The survey, based on questions asked of Royal College of General Practitioners (RCGP) members in 1999, and covering letter were electronically sent to GPs between May and August 2017 via various primary care dissemination routes. Results: Four hundred and twenty-eight GPs responded. Suspected Infection in the elderly, recurrent urinary tract infection (UTI), surveillance of AMR in the community, leg ulcers, persistent cough and cellulitis all fell into the top six conditions ranked in order of importance that require further research, evidence and guidance. Acute sore throat, otitis media and sinusitis were of lower importance than in 1999. Conclusion: This survey will help the NHS, the UK National Institute for Health and Care Excellence (NICE) and researchers to prioritise for the development of guidance and research for chronic conditions highlighted for which there is little evidence base for diagnostic and management guidelines in primary care. In contrast, 20 years of investment into research, guidance and resources for acute respiratory infections have successfully reduced these as priority areas for GPs.